Circus practices and university extension: Facing social inequality during pandemic - Kronbauer, Gláucia Andreza; Magnabosco Martins, Claudia Regina (Guará Journal, 2022)
This  text  aims  to  present  and  discuss  the  strategies found  by  the extension project “Circo em Contextos”, in association to the “Central for Support and Integration of Projects and Collective Actions”, from UNICENTRO, Irati, to develop its actions during the period of social distancing due to the pandemic caused by COVID-19. The children were especially affected by the process of social distancing. In a very unique way they were kept away fromhool  and  restricted  their  development opportunities.  Ac-tions  were  carried  out  in  an attempt  to  minimize  the  effects  of  pandemic  among the  most  vulnerable  populations.  Every  two  weeks, “solidarity  banks  or  hangers”  were  organized  in  the suburbs of Irati. Those who had something to donate and/or  exchange  deposited  their  products  and  those who  need  could pick up the products, only for their own use. Food, personal  hygiene  and  cleaning products,  clothes,  books,  peda-gogical activities and toys were collected and donated. Circo em  Contextos produced  teaching  materials  about  Circus  for donation.  From  these  experiences,  we  argue  that  the know-ledge and practices promoted by/in university extension hold the  potential  for  valuable  contributions to  education  and  to  serve the community, even in times of exception, such as those experienced during the Covid-19 pandemic.
Keywords: University extension; Collective actions; Circus; Education; Pandemic; COVID-19